Effects of dipeptidyl peptidase-4 inhibitor in insulin-resistant rats with myocardial infarction - Nattayaporn Apaijai (2018)
© 2016 Society for Endocrinology. Adverse cardiac remodeling after myocardial infarction (MI) leads to progressive heart failure. Obese-insulin resistance increases risks of MI and heart failure. Although dipeptidyl peptidase-4 (DPP4) inhibitor is known to exert cardioprotection, its effects on adverse remodeling after MI in obese-insulin-resistant rats are unclear. We hypothesized that DPP4 inhibitor reduces adverse left ventricular (LV) remodeling and LV dysfunction in obese-insulin-resistant rats with MI. Rats were fed either normal diet (ND) or highfat diet (HFD) for 12 weeks to induce obese-insulin resistance, followed by left anterior descending coronary artery ligation to induce MI. Then, rats in each dietary group were divided into five subgroups to receive vehicle, enalapril (10 mg/kg/day), metformin (30 mg/kg/day), DPP4 inhibitor vildagliptin (3 mg/kg/day), or combined metformin and vildagliptin for 8 weeks. Heart rate variability (HRV), LV function, pathological and biochemical studies for LV remodeling, and cardiomyocyte apoptosis were determined. Obese-insulin-resistant rats had severe insulin resistance and LV dysfunction. HFD rats had a higher mortality rate than ND rats, and all treatments reduced the mortality rate in obese-insulin-resistant rats. Although all drugs improved insulin resistance, HRV, LV function as well as reduced cardiac hypertrophy and fibrosis, vildagliptin effectively reduced cardiomyocyte cross-sectional areas more than enalapril and was related to markedly decreased ERK1/2 phosphorylation. In ND rats with MI, metformin neither improved LV ejection fraction nor reduced cardiac fibrosis. The infarct size and transforming growth factor-ß expression were not different among groups. In obese-insulin-resistant rats with chronic MI, DPP4 inhibitor vildagliptin exerts better cardioprotection than enalapril in attenuating adverse LV remodeling.